The generals of Gettysburg : the leaders of America's greatest battle - Tagg, Larry (Campbell, California : Savas Publishing Company, 1998)
Short biographies of the Generals in the Civil war.
The Army of the Potomac. General George G. Meade and the Army of the Potomac -- John Reynolds and the First Corps -- Winfield Hancock and the Second Corps -- Daniel Sickles and the Third Corps -- George Sykes and the Fifth Corps -- John Sedgwick and the Sixth Corps -- Oliver Howard and the Eleventh Corps -- Henry Slocum and the Twelfth Corps -- Alfred Pleasonton and the Cavalry Corps -- Henry Hunt and the Federal Artillery. The Army of Northern Virginia. General Robert E. Lee and the Army of Northern Virginia -- James Longstreet and the First Corps -- Richard S. Ewell and the Second Corps -- Ambrose P. Hill and the Third Corps -- James "Jeb" Stuart and the Cavalry Division -- William Pendleton and the Confederate Artillery.
Includes bibliographical references.
Keywords: 1861-1865; Generals -- United States -- Biography; Gettysburg, Battle of, Gettysburg, Pa., 1863.; Bataille de Gettysburg, Gettysburg, Penns., 1863.; Military campaigns; Generals; Sezessionskrieg; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States, Pennsylvania, Adams, Gettysburg -- Military history -- Civil War, 1861-1865 -- Biography; Gettysburg (Pa.) -- Schlacht; Biography; History